Firm Efficiency and the Regulatory Closure of S&Ls: An Empirical Investigation - Cebenoyan, A. Sinan; Cooperman, Elizabeth S.; Register, Charles A. (The Review of Economics and Statistics, 1993)
This paper uses a two-step methodology to examine the relationship between firm inefficiency and the regulatory closure of savings and loans (S&Ls). In the first step, using multiproduct, translog stochastic cost frontiers, the authors estimate inefficiency scores separately for mutual and stock S&Ls operating in the Southwest in 1988. They use the inefficiency scores in second step logit models to identify determinants of regulatory closure. For both mutual and stock S&Ls, the authors find a significant positive relationship between firm inefficiency and regulatory closure. They also find a greater probability of closure for S&Ls in economically depressed states. Copyright 1993 by MIT Press.